Tinjauan Atas Layanan Prima Pada Hotel Onih Bogor - Fadillah, Muhammad Faiz; Purnama, Denta (Jurnal Ilmiah Pariwisata Kesatuan, 2023)
ABSTRACTDevelopment in all sectors is the goal and target of society, in line with development in all sectors, especially the hotel industry, one of which has the potential to receive serious treatment is the hotel industry sector. The hotel industry is very competitive and hotels must strive to improve excellent service to retain and increase the number of hotel customers. Companies need to have an understanding of excellent service as one of the steps in increasing customer satisfaction, building a positive reputation, and increasing the level of customer satisfaction and loyalty.The purpose of this review is to gain an understanding of: 1) How excellent service is implemented at the Onih Bogor Hotel; 2) What are the obstacles to excellent service at the Onih Bogor Hotel; 3) How to overcome problems with excellent service at the Onih Bogor Hotel.The results of this review are: 1) Hotel Onih Bogor has implemented the elements of excellent service at Hotel Onih Bogor; 2) Obstacles that occur include: a) The high number of customers who need to be served simultaneously at the front office, b) Special requests that are difficult to fulfill due to limited goods, especially iron, c) Disturbances in providing good wifi or internet facilities; 3) Efforts to overcome the obstacles that occur include: a) Front office staff arranging customers to wait on the sofa in the hotel lobby, b) Arranging ironing loan schedules and suggesting the use of laundry services as an alternative to fulfill customer requests regarding irons, c) Hotel staff helping customers looking for better quality wifi networks, such as using wifi in meeting rooms. Keyword : Excellent Service